Development of a Fuzzy Logic Controller (FLC) for a Chicken Feather Plucking Machine. - Alim, S. A.; Abdullateef, I. A.; Shobowale, K. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Feathers are epidermal growths or flat appendages that form a unique exterior covering, or plumage, on (avian) birds, some non-avian and possibly other archosauromorphs. They are regarded as the most complicated skin structures observed in vertebrates. The traditional method of manually plucking the feathers with the hand is still the common practice in Nigeria for both private and commercial use. For both manual and machine plucking, the chicken must have undergone scalding. In an attempt to add some form of intelligence to the design of the mechanical chicken feather plucking machines, a fuzzy logic controller (FLC) is developed for this system. Compared to conventional control techniques, FLC has been best applied in complex ill-defined problems, which can be controlled by an efficient human operator without knowledge of their underlying dynamics. In the design of the FLC, two input parameters were considered namely scalding temperature and weight of the chicken. While the output parameters considered were the rotating speed and rotating time of the plucker. Nine rules were developed to effect the control process. For a chicken of 2.0kg weight and temperature of 80°C, the rotating speed and plucking time are 402rpm and 20.3secs. It shows the proof of concept that the chicken feather plucking process can be automated.